Measures to achieve carbon neutrality: What is the role of energy structure, infrastructure, and financial inclusion. (1st January 2023) - Hussain, Muzzammil; Lin, Yuxiao; Wang, Yiwen
Abstract: Infrastructure and energy structure play key roles in the adaptation of a sustainable environment. In order to achieve a desirable infrastructure and energy structure, financial inclusion is essential. Thus, the current study investigates the nexus of energy structure, infrastructure, financial inclusion, and carbon emissions in the countries of the Organization for Economic Co-operation and Development (OECD). In particular, the well-known nexus of growth and environment is employed to estimate the linkages using data between 2001 and 2020. The findings suggest the supportive role of infrastructure, energy structure, and financial inclusion in abating carbon emissions. The OECD economies should enhance their investment in infrastructure and energy structure. Moreover, in order to achieve a sustainable environment in the long-run, financial inclusion should also be expanded. The results are also robust to the short- and long-run policy implications. This study is conductive to the implementation of the United Nations (UN) Sustainable Development Goals. Highlights: Infrastructure, Energy structure, financial inclusion, and CO2 emissions' linkages are re-examined. Robust econometric estimations are applied. Energy structure, infrastructure, and financial inclusion are found to support the reduction of carbon emissions. A high population is a hurdle to a sustainable environment.